Medical and surgical stroke - Kase, Carlos (Henry Stewart Talks, 2008)
Cerebrovascular complications of medical interventions and invasive procedures, Cardiac catheterization and cerebral embolism, Risk factors for stroke and patterns of cerebral damage during cardiac surgery
Archived at 2021/02/25